The dynamics of perception and trust in decision-making among MSMEs: Insights from Islamic banking financing - Deswara, Nida Indika (Center for Economics, Business and Entrepreneurship Development Faculty of Economics and Business, Universitas Muhammadiyah Malang, 2023)
This study aims to investigate the impact of perception and trust on MSMEs' decisions regarding Islamic bank financing. Data were collected from 87 MSMEs in Ngaliyan District, Semarang, through surveys and questionnaires. Using a quantitative approach, the data were analyzed with IBM SPSS Statistics Version 24, employing multiple regression analysis. Surprisingly, the results show that neither perception nor trust significantly influences MSME entrepreneurs' decisions. Instead, factors like convenience and efficiency play a more critical role. The study emphasizes the need to streamline processes and improve accessibility to better serve MSMEs.